2022
DOI: 10.1111/hsc.13704
|View full text |Cite
|
Sign up to set email alerts
|

Yes, I can (with you)! Dyadic coping and self‐management outcomes in cardiovascular disease: The mediating role of health self‐efficacy

Abstract: Cardiac patients show alarming levels of nonadherence to medications. It is important to consider also patient activation levels. Furthermore, the partner could have a supporting role in these processes. The aim of this study was to investigate the mediating role of patient health self-efficacy (HSE) in the link between dyadic coping (DC) and two self-management outcomes (i.e. medication adherence and patient activation) across the first 6 months of cardiac disease. One hundred couples completed two self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 102 publications
0
21
0
Order By: Relevance
“…Importantly, patient outcomes and those of their caregivers are typically interdependent, as characteristic of dyadic processes in intimate relationships. This means that the outcomes of one member of the dyad influence the outcomes of the other member and vice versa, as shown in studies involving the non-clinical population (e.g., Donato et al, 2015 ), patients with cardiovascular problems (e.g., George-Levi et al, 2016 ; Rapelli et al, 2021 , 2022a ), and with LVAD specifically ( Bidwell et al, 2018 ; Rossi Ferrario and Panzeri, 2020 ).…”
Section: Introductionmentioning
confidence: 97%
“…Importantly, patient outcomes and those of their caregivers are typically interdependent, as characteristic of dyadic processes in intimate relationships. This means that the outcomes of one member of the dyad influence the outcomes of the other member and vice versa, as shown in studies involving the non-clinical population (e.g., Donato et al, 2015 ), patients with cardiovascular problems (e.g., George-Levi et al, 2016 ; Rapelli et al, 2021 , 2022a ), and with LVAD specifically ( Bidwell et al, 2018 ; Rossi Ferrario and Panzeri, 2020 ).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, this study showed that patient activation, health literacy and disease knowledge explained only approximately 25% of the total variance in the self-care behaviours of older HF patients. According to recent studies regarding the role of partners in patient activation among cardiac patient, partners may be a key resource in HF management because partner presence can contribute to or impede activation in patients' self-care behaviours (Rapelli et al, 2020(Rapelli et al, , 2022. Unfortunately, this study did not include additional information on partner or spouse such as relationship quality and type of caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding was in line with preview studies 2,4–6 and strongly highlighted the impact of psychological and behavioral interplay in cardiovascular risk. Cardiac disease could be affected in the first time of primary care to the low adherence to the medication drawing and alarming level for self‐management of health in long time 22,23 . Emotional regulation appeared the mechanisms to take care in clinical setting for adherence to medication 11,24 .…”
Section: Discussionmentioning
confidence: 99%